$(p,q)$-Analytic functions and a complex $(p,q)$-binomial formula - Gençtürk, İlker (Ukrains’kyi Matematychnyi Zhurnal, 2025)
UDC 517.5We introduce the notions of $(p,q)$-differential for complex discrete functions and $(p,q)$-complex differential operators in a sense of Pashaev. The $(p,q)$-analog of the $q$-binomial formula is presented and the $(p,q)$-Taylor expansion is constructed for $(p,q)$-analytic functions. These results provide a generalized framework for $(p,q)$-calculus, contributing to its applications in mathematical analysis and related fields.